PENGATURAN BISNIS PINJAMAN SECARA ONLINE ATAU FINTECH MENURUT HUKUM POSITIF DI INDONESIA - ARI RAHMAD HAKIM BF; I GUSTI AGUNG WISUDAWAN; YUDI SETIAWAN (Universitas Mahasaraswati Mataram, 2020)
Online credit lending or referred to as “Fintech” is now developing in Indonesian society and is considered as a solution to get loans without collateral for consumptive purposes. The development of Fintech certainly requires supervision by the Financial Services Authority (OJK). This research is a normative research with a statutory approach, conceptual approach, and case approach. This study also uses primary, secondary , and tertiary legal materials. The technique of collecting legal materials used in this research is the study of legal documentation, then analyzed in a qualitative descriptive manner. The results show that: 1). Online credit loan or fintech business arrangements according to positive law in Indonesia are regulated by Bank Indonesia Regulation, No 18/40 / PBI / 2016 and No 19/12 / PBI / 2017, Member of the Board of Governors Regulation No. 19/14 / PADG / 2017 and No 19/15 / PADG / 2017. 2), the form of supervision carried out by the Financial Services Authority (OJK) of the online credit business is an integrated and coordinated supervision system between legal structures such as the Police, BI. OJK, and Investment Alert Task Force